The Geology of Montserrat, British West Indies - Rea, W; Rea, William J. (1970)
﻿ The Island of Montserrat lies towards the northern end of the Lesser Antilles. It is made up of the products of five major and three smaller, parasitic volcanic centres. The four oldest volcanoes occur in the northern half of the island. Products of these volcanoes include andesitic lavas and pyroclastics but there is a lack of unreworked fragmental deposits and primary volcanic structures so that it is difficult to reconstruct the volcanic history of these centres. It appears however that the Harris-Bugby Centre, where a two-pyroxene andesite lava gave a K-Ar of 4.1 m.y. is the oldest volcano on Montserrat. Silver Hill where a late-stage (?) lava has a K-Ar age of 1.5 m.y. is older than the Centre Hills and Carabald Hill should probably be regarded as a parasitic centre of the Centre Hills in view of the similarity of the products and state of erosion of the two volcanoes. The oldest volcano in the south of Montserrat is South Soufriere Hill, where eruptions may have begun as much as 1.6 m.y. ago. The products of this volcano include basaltic lava flows and a well-exposed sequence of andesitic and basaltic pyroclast falls, known as the White River Pyroclast Fall Series. Ultrabasic cumulate blocks occur within an andesite block fall of the White River Pyroclast Fall Series. It is thought that the lava flows and pyroclast falls built up a cone-shaped strato-volcano with a large central crater. Late in the history of Smith Soufriere Hill two basic domes were extruded within the crater and their extrusion destroyed most of the crater wall and much of the eastern flank of the strato-volcano. The intrusion at Roche's of a body of basic two-pyroxene andesite of similar composition to the domes at South Soufriere Hill may also have occurred about this time. Among deposits disturbed by this intrusion are a group of tuffaceous limestones which on palaeontological grounds are thought to be about 40,000 yrs. old. Because of the compositional similarity of the Roche's Intrusion and the South Soufriere Hill domes and because the intrusion has affected deposits which are similar to South Soufriere Hill pyroclast falls the Roche's Centre is probably a subsidiary centre of South Soufriere Hill. The earliest events at the Soufriere Hills included the extrusion of of two-pyroxene andesite and associated pyroclast flow eruptions. These were followed by the extrusion of at least two domes of hornblende-hypersthene andesite and charcoal from a pyroclast flow believed to have been associated with one of these domes gave an age of 23,568 andplusmn; 786 yrs. St. George's Hill which erupted large quantities of hornblende-hypersthene andesite pumice falls may have been active as a subsidiary centre on the north west flank of the Soufriere Hills about this time. Sometime after the extrusion of the hornblende-hypersthene andesite domes violent pumice flow eruptions gave rise to the formation of English's Crater. Charcoal from one of the pumice flows has given an age of 18,390 andplusmn; 360 yrs. Late stage events at the Soufriere Hills include the extrusion of the Castle Peak hornblende-hypersthene andesite dome within the crater and this may be related to the breaching of the east wall of the crater. Minor eruptions of pyroclast flows and pyroclast falls have occurred since the formation of Castle Peak and charcoal from the most recent of these has been dated at A.D. 1646 ± 54 yrs. Although there have been no recorded eruptions at the Soufriere Hills solfataric activity has been continuous in historic time and three periods of unusually intense seismic and solfataric activity have occurred within the last 70 years. An estimate of the relative volumes of rock types on Montserrat shows that andesite (96.5%) greatly predominates over basalt (3.3%) and dacite (0.2%). Basalts occur only at South Soufriere Hill where they account for about 35% of the total volume. South Soufriere Hill with its ultrabasic cumulates, basalts, basaltic andesites and andesites resembles Mt. Misery, St. Kitts or the Soufriere, St. Vincent. The other Montserratian volcanoes and most volcanoes in the Lesser Antilles have erupted nothing but andesite. The Montserrat basalts and andesites have many petrographical features in common with other calc-alkaline lavas. Plagioclase which is the most abundant phenocryst mineral has highly calcic cores (~An85) which may reflect initial crystallisation under high water vapour pressures. Olivine (~Fo75) was apparently the first phenocryst to form in the basalts. There is some evidence of a reaction relation between u and liquid to produce hypersthene but olivine is more often surrounded by clinopyroxene coronas than by hypersthene rims. Magnetite which is more abundant in the basalts than the andesites may also have been an early phase to separate. Pyroxene phenocrysts in the basalts and andesites show complex interrelationships. There is, however, no evidence to suggest a reaction relationship between augite and liquid to give hypersthene. Instead clinopyroxene probably reacts with liquid to give hornblende, which will account for the antipathetic relationship between these minerals in the Montserrat lavas. Microphenocrysts in the lavas have different compositions and properties to the phenocrysts and are believed to have crystallised at higher levels in the crust probably close to the surface. Phenocrysts which initially formed deeper in the crust may undergo additional crystallisation at this stage. A notable feature of the groundmasses of the Montserrat lavas is the abundance of tridymite and cristobalite, which appear to have crystallised at a very late stage, perhaps from fluids tripped in lavas at the time of their eruption. A few lavas contain quartz rich mica-bearing aggregates which have a similar mode of occurrence to tridymite and cristobalite in the other rocks. The mica is probably phlogopite. Disequilibrium petrographic features are common in the Montserrat lavas. Lowering of water vapour pressure may account for the resorption of quartz, hornblende and calcic plagioclase at shallow depths. Oscillatory zoning in plagioclase might reflect small fluctuations in water vapour pressure but is probably best explained in terms of a diffusion-supersaturation theory. Four groups of xenoliths were recognised on Montserrat. Ultrabasic cumulates composed of unzoned crystals of sodic anorthite (~An90), aluminous amphibole, olivine (~Fo75) and magnetite occur within andesitic pyroclastics of the White River Pyroclast Fall Series. They have probably formed by the crystallisation of basaltic magma under high water vapour pressures at depths of ?6andndash;8 km. Rare doleritic blocks also occur in andesitic horizons of the White River Pyroclast Fall Series. Cognate xenoliths of basaltic composition are found in andesitic lavas and represent accumulations of minerals which occur as microphenocrysts in the host rock together with a few "older" phenocrysts. Metasedimentary and metavolcanic blocks were also found on Montserrat. Forty-five new major element analyses together with new determinations of 13 trace elements in 13 rocks and Sr87/86 ratios in 7 rocks are presented along with some older analytical data. These data suggest that the Montserrat lavas form a closely related series of rocks. The rocks of South Soufriere Hill however, differ from those of the other Montserratian volcanoes in that their SiO2 range is larger and the South Soufriere Hill andesites are slightly depleted in total iron, MgO, TiO2 and V and slightly enriched in Na2O and Al2O3 relative to andesites from the other volcanoes. Petrochemically, the Montserrat lavas resemble those from most of the other islands in the Lesser Antilles, especially St. Kitts. However they have less K2O, Rb, Ba and Cr and more Na2O, V, Co and Cu than lavas from St. Lucia and lower Sr87/86 ratios and smaller amounts of radiogenic lead than lavas from St. Lucia and Dominica. The Montserrat lavas also bear an overall chemical resemblance to lavas from other calc-alkaline suites but they are somewhat depleted in TiO2, Rb, Sr, Ba, Ni and Cr and enriched in Al2O3 and CaO compared with most calc-alkaline lavas especially those from continental areas. Basalts from Montserrat contain slightly more K2O than most high alumina basalts but the Montserrat andesites are considerably depleted in K2O relative to most andesites. The fundamental process in the petrogenesis of the Montserrat lavas is believed to involve the partial melting of oceanic tholeiite, or its metamorphosed equivalent along the Benioff Zone beneath the Lesser Antilles. Oceanic tholeiite is a suitable parent for the Montserrat and the Lesser Antillean lavas in terms of composition and availability. The only difficulty is that the Lesser Antillean lavas, particularly those from St. Lucia and Dominica are so enriched in the large and highly charged cation elements and radiogenic nuclides compared with oceanic tholeiite that an extra source for these appears to be required. Relatively small amounts of alkali basalt, oceanic sediment and detritus from South America or the Lesser Antilles may be carried into the upper mantle and melted with the oceanic tholeiite and these are possible sources of the "missing" elements and also of water. The composition of the magmas resulting from the melting of material along the Benioff Zone will vary depending on the physical conditions. Low temperatures and hydrous conditions will favour the production of andesitic liquids whereas dry melting and high temperatures will tend to produce basaltic liquids. As the arc evolves the tendency is probably towards wetter melting conditions as more material from the arc or more oceanic sediment does down the Benioff Zone. As the magmas generated along the Benioff Zone ascend to the surface they may be modified by a number of secondary processes. These include fractional crystallisation, wallrock reaction, assimilation and gas transfer. There is evidence in the Lesser Antillean rocks for at least two periods of fractional crystallisation. One of these occurs near the surface, at low pressures and probably has little fundamental petrogenetic effect. The other, which occurs deeper in the crust (? 6andndash;8 km.) involves the separation of sub-silicic aggregates from basaltic magma and is probably instrumental in producing andesites at certain volcanoes in the Lesser Antilles, like South Soufriere Hill, Montserrat and Soufriere, St. Vincent. The relative importance of the other "secondary" processes is rather difficult to assess. Wall rock reaction does not appear to be very important within the mantle but may occur within the crust. Gas transfer is likely to be quite important especially in water rich magmas and may be in some measure responsible for the erratic behaviour of certain elements notably K2O in the Lesser Antillean lavas. The compositional variation within the Lesser Antilles may to some extent reflect differences in the relative importance of different "secondary" petrogenetic processes at different places. The restriction of chemically "evolved" lavas to the islands of St. Lucia, Dominica. and ?Martinique in the central portion of the arc may, however reflect the fact that these islands are the oldest in the Lesser Antilles although their position relative to the direction of underthrusting of oceanic crust might also be important.